The Role of MGMP Civic Education in Improving Professional Competence of Teacher - Arifin Arifin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This study aimed to describe the role of Musyawarah Guru Mata Pelajaran (MGMP) Civic Education in Malang City in enhancing the professional competence of teachers and to know the efforts in Increasing the professional competence of teachers. The researcher used qualitative descriptive method. Data collection techniques used observation, interview, and documentation. The results showed that the teachers of Musyawarah Guru Mata Pelajaran (MGMP) Civic Education played an active role in helping teachers to improve their professional competence. The effort in increasing the professional competence of teachers namely, conducts a seminar by inviting competent speakers. Keywords: MGMP, Civic Education, Professional Competence of Teacher